Dissemination of Thinking while Moving in Maths: Implementation Barriers and Facilitators. Issue 1 (6th January 2021) - Riley, Nicholas; Mavilidi, Myrto F.; Kennedy, Sarah G.; Morgan, Philip J.; Lubans, David R.
ABSTRACT: Integrating physical activity into the curriculum can reduce the time children spend sedentary and enhance the learning experience, particularly in mathematics where engagement is a real concern. The aim of the current study was to evaluate the dissemination of the Thinking while Moving in Maths (TWM-M) professional learning program guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance framework. During 2016–2018, 21 TWM-M teacher professional learning workshops were delivered across New South Wales, Australia. A total of 482 teachers from 282 elementary schools attended the workshops. A stratified random sample of participants completed either a follow-up survey ( n = 18) or were interviewed using a semistructured discussion framework ( n = 13). Teachers reported increased student engagement in mathematics when a movement-based pedagogy was used, which had been reported as the main reason for attending the professional learning workshop (Reach). TWM-M had a positive effect on students' enjoyment and motivation to learn mathematics (Effectiveness). Workshop attendance improved teachers' skills and confidence to deliver movement-based mathematics (Adoption). TWM-M was implemented through a variety of delivery modes, including whole class lessons outside the classroom, with 5- to 10-min energizer breaks during mathematics lessons inside the classroom (Implementation). Implementation issues and the need for additional resources emerged as barriers to whole school adoption. The TWM-M program had reached students at the class level. However, evidence for whole school adoption and delivery outside the particular stage is limited (Maintenance). The TWM-M program was successfully disseminated in New South Wales elementary schools. Programs designed to increase children's physical activity and enhance their academic outcomes are likely to be attractive to teachers, if they are designed in partnership with education authorities. Overall, the TWM-M professional learning program was positively received. Novel strategies need to ensure that professional learning delivered off site has effect on the whole school level.